2012
DOI: 10.1186/preaccept-4573938456623837
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of endoluminal interventional therapy in diabetic peripheral arterial occlusive disease: a retrospective trial

Abstract: Background: The purpose of this study was to assess the efficacy of interventional therapy for peripheral arterial occlusive disease and the difference between diabetic patients and non-diabetic patients.Methods: 139 consecutive patients between September 2006 and September 2010 who underwent percutaneous lower extremity revascularization for arterial lesions were divided into diabetes group (n = 62) and non-diabetes group (n = 77). Before intervention, rest ankle brachial indexes and three dimensional compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Eight studies discussed primary patency (n = 3230). 13,17,20,25,27-30 Among the 8 studies, 4 showed a significantly positive relationship between DM and poor primary patency. However, the RR varied widely between studies, ranging from 0.37 to 1.19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies discussed primary patency (n = 3230). 13,17,20,25,27-30 Among the 8 studies, 4 showed a significantly positive relationship between DM and poor primary patency. However, the RR varied widely between studies, ranging from 0.37 to 1.19.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that there was no significant difference in the limb salvage rate between the diabetic and non-diabetic groups (RR: 0.98; 95% CI: 0.91–1.05). 13,17,19,20,23,28,30-32 No clear risk factors were found after subgroup analysis according to the type of treatment following adjustment for confounding factors and the degree of PAD (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the study conducted by Levigne et al [21], it was found that there were higher amputation rates after endovascular interventions in the diabetic patient group, which was associated with hyperglycemia, reducing the tolerance of tissue ischemia. Xiao et al [22] conducted a study and evaluated the effectiveness of endovascular treatment in limb-threatening leg ischemia, and reported that there were no differences between the diabetic and non-diabetic patient groups in terms of 12-month primary and secondary patency and limb recovery rates. In the literature, up to 70% amputation rates were reported in limb-threatening leg ischemia patients, which were 5 times more common in diabetic patients [23,24].…”
Section: Discussionmentioning
confidence: 99%